2015
DOI: 10.1016/j.dcn.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural correlates of complex sentence comprehension in children

Abstract: HighlightsChildren between 5 and 8 years performed a sentence comprehension task.Their structural images were analyzed using voxel-based morphometry.Gray matter in inferior temporal and frontal areas predicts thematic role assignment.Left temporo-parietal area's gray matter predicts working memory-related performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 86 publications
0
13
2
1
Order By: Relevance
“…The acquisition and processing of recursive or center-embedded structure is a difficult and complicated cognitive process, as revealed by studies in the field of language and other cognitive disciplines. Developmental studies have revealed that although children grasp basic and simple syntax with surprising speed, they cannot exactly grasp non-adjacent syntax involving a center-embedded structure until the age of 7 years (Schipke et al, 2012 ; Fengler et al, 2015 ; Skeide and Friederici, 2016 ). Studies directly comparing the online processing of center-embedded vs. non-embedded sentences have found that processing of the verbs in matrix clauses marking the complication of long-distance dependency in embedded sentences is more difficult than processing the verb in non-embedded sentences, indicated by slower reaction times (Stromswold et al, 1996 ), lower accuracy rate (Opitz and Friederici, 2007 ) and larger ERPs, such as LAN or P600 (Vos et al, 2001 ; Phillips et al, 2005 ; Li and Zhou, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition and processing of recursive or center-embedded structure is a difficult and complicated cognitive process, as revealed by studies in the field of language and other cognitive disciplines. Developmental studies have revealed that although children grasp basic and simple syntax with surprising speed, they cannot exactly grasp non-adjacent syntax involving a center-embedded structure until the age of 7 years (Schipke et al, 2012 ; Fengler et al, 2015 ; Skeide and Friederici, 2016 ). Studies directly comparing the online processing of center-embedded vs. non-embedded sentences have found that processing of the verbs in matrix clauses marking the complication of long-distance dependency in embedded sentences is more difficult than processing the verb in non-embedded sentences, indicated by slower reaction times (Stromswold et al, 1996 ), lower accuracy rate (Opitz and Friederici, 2007 ) and larger ERPs, such as LAN or P600 (Vos et al, 2001 ; Phillips et al, 2005 ; Li and Zhou, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, gray matter density decreases along development, with higher-order association regions decreasing later than lower-order sensorimotor regions ( Brain Development Cooperative Group, 2012 , Gogtay et al, 2004 ). Specifically, gray matter in those frontal and parietal brain regions that are involved in sentence processing in adults (for a review, see Friederici, 2011 ) only appears to decrease between 7 and 12 years ( Giedd et al, 1999 , Sowell et al, 2003 ), and recent structural imaging data have shown that the structural integrity of these regions correlates with the crucial cognitive abilities underlying complex sentence comprehension ( Fengler et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ako se osvrnemo na prediktivnu varijablu pamćenja brojeva unatrag, prema Baddeleyevu modelu (Gathercole i Baddeley, 1993) radi se o središnjem izvršitelju, nadređenoj sastavnici radnog pamćenja, koji prebacuje pažnju, potiskuje manje važne informacije sprječavajući njihovo ometanje djelovanja radnog pamćenja i obnavlja njegov sadržaj otpuštajući informacije koje više nisu relevantne. Radno pamćenje najistraživanija je sastavnica izvršnih funkcija te se u velikom broju DOI: 10.21465/2017-SP-201-04 istraživanja pokazala povezanom s obradom rečenica (Fengler, Meyer i Friederici, 2015;Martin i sur., 2007). Većina slučajeva u kojima se pokazalo povezanim, bili su upravo slučajevi sintaktički ili semantički složenih ili dvosmislenih rečenica koje su zahtjevnije za obradu.…”
Section: Raspravaunclassified